Clinical coaches in nursing and midwifery practice: Facilitating point of care workplace learning and development. Issue 4 (August 2017) - Faithfull-Byrne, Annette; Thompson, Lorraine; Schafer, Keppel W.; Elks, Michelle; Jaspers, Jenny; Welch, Anthony; Williamson, Moira; Cross, Wendy; Moss, Cheryle
Abstract: Contemporary demands for workplace learning and development in real time have guided one health service to create a new role, that of the clinical coach. Clinical coaches provide point of care educational interventions to achieve clinical skill and practice development for nurses and midwives and to stimulate a culture of learning and development within the organisation. Clinical coaches use coaching processes and mantras, facilitation skills, practice development principles, adult learning strategies, supported practice and clinical assessment tools to achieve these goals within a person-centred philosophy. Specific point of care accountabilities of the coaches related to staff development include supporting clinical induction requirements, supporting preceptor and learner practices, supporting evidence-based clinical development, ensuring that mandatory training requirements are met, and coaching for the maintenance of safe and competent practice. The clinical coach role has evolved throughout the health service over a number of years. Organisational data reveal the acceptability of the coaching role in the organisation along with successful outcomes. Based on this case experience, it is recommended that other health services consider clinical coaching as a relevant mechanism for advancing point of care workplace integrated learning and development.